2022
DOI: 10.1021/jasms.2c00162
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Halogenated Molybdenum Sulfide Dianions [Mo3S7X6]2–(X = Cl, Br, I)

Abstract: Molybdenum sulfides are considered a promising and inexpensive alternative to platinum as a catalyst for the hydrogen evolution reaction. In this study, we perform collision-induced dissociation experiments in the gas phase with the halogenated molybdenum sulfides [Mo3S7Cl6]2–, [Mo3S7Br6]2–, and [Mo3S7I6]2–. We show that the first fragmentation step for all three dianions is charge separation via loss of a halide ion. As a second step, further halogen loss competes with the dissociation of a disulfur molecule,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The ions are transferred into the ICR cell of the FT-ICR MS, where the cluster size of interest is isolated. Sustained off-resonance irradiation (SORI) 41 collision induced dissociation (CID) experiments are performed [42][43][44] using argon (99.999%) as collision gas at constant pressures between 0.8 Â 10 À8 mbar and 1.0 Â 10 À8 mbar. The parameters for the SORI CID experiment were set to a pulse length of 1.0 s and a frequency offset of 500.0 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The ions are transferred into the ICR cell of the FT-ICR MS, where the cluster size of interest is isolated. Sustained off-resonance irradiation (SORI) 41 collision induced dissociation (CID) experiments are performed [42][43][44] using argon (99.999%) as collision gas at constant pressures between 0.8 Â 10 À8 mbar and 1.0 Â 10 À8 mbar. The parameters for the SORI CID experiment were set to a pulse length of 1.0 s and a frequency offset of 500.0 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Gas‐phase fragmentation studies showed that loss of the terminal halides is the energetically most feasible fragmentation route, lending further support to the concept of preferred exchange at the terminal ligand sites. [ 48 ] In a follow‐up work, Ončák and colleagues further linked thermochemical data calculated by DFT to experimental Fourier‐transform ion‐cyclotron resonance mass spectrometry (FT‐ICR MS) and infrared multiple photon dissociation (IRMPD) spectroscopy data measured for a singly protonated [HMo 3 S 13 ] − species. [ 49 ] The authors reported that under their conditions (in the gas phase), only the Mo 3 ‐based species with a singly protonated terminal disulfide ligand is observed.…”
Section: Catalytic Performance and Active Sitesmentioning
confidence: 99%